Let 'd' be the perpendicular distance from the centre of the ellipse
![\frac{ {x}^{2} }{ {a}^{2} } + \frac{ {y}^{2} }{ {b}^{2} } = 1 \frac{ {x}^{2} }{ {a}^{2} } + \frac{ {y}^{2} }{ {b}^{2} } = 1](https://tex.z-dn.net/?f=+%5Cfrac%7B+%7Bx%7D%5E%7B2%7D+%7D%7B+%7Ba%7D%5E%7B2%7D+%7D++%2B++%5Cfrac%7B+%7By%7D%5E%7B2%7D+%7D%7B+%7Bb%7D%5E%7B2%7D+%7D++%3D+1)
to the tangent drawn at a point P on the ellipse.
If
are the two focii of the ellipse, then show that,
![{(PF_1-PF_2)}^{2}=4{a}^{2}(1-\frac{{b}^{2}}{{d}^{2}}) {(PF_1-PF_2)}^{2}=4{a}^{2}(1-\frac{{b}^{2}}{{d}^{2}})](https://tex.z-dn.net/?f=%7B%28PF_1-PF_2%29%7D%5E%7B2%7D%3D4%7Ba%7D%5E%7B2%7D%281-%5Cfrac%7B%7Bb%7D%5E%7B2%7D%7D%7B%7Bd%7D%5E%7B2%7D%7D%29)
✔️✔️Proper solution needed✔️✔️
Answers
Answered by
9
ANSWER
Plz refer to the attachment for diagram.
Step By Step Explanation
Let the coordinates of P be ( )
Now, equation of tangent at P is >
= 1
Now,
d =
=>
=
Now,
RHS
=>
=>
=>
=>
=>
=>
=>
Again,
=>
=>
Similarly we have >
Now,
RHS
=>
=>
=>
Hence , LHS = RHS
Proved
Attachments:
![](https://hi-static.z-dn.net/files/de9/898e7b6f8a50e94e83e47987ad41d05d.jpg)
Anonymous:
r u online?
Similar questions